Use of Hydroxyapatite Nanoparticles to Reduce Cd Contamination in Agricultural Soils: Effects on Growth and Development of Chenopodium quinoa Willd - Rocío González-Feijoo; Cecilia Martínez-Castillo; Vanesa Santás-Miguel; Daniel Arenas-Lago; Paula Pérez-Rodríguez (Applied Sciences)
Soil contamination and degradation have prompted extensive research into remediation techniques. A promising approach involves the use of nanoparticles, which can mitigate heavy metal contamination, such as cadmium (Cd), without adversely affecting crop development. This study evaluated the effects of hydroxyapatite nanoparticles (HANPs) on the growth of Chenopodium quinoa Willd. in soils contaminated with varying Cd contents (0, 5, 10, 25, and 50 mg/kg). The results indicated that HANPs enhanced early shoot development, particularly in soils with Cd concentrations ≥10 mg/kg, while significantly reducing Cd accumulation in plant tissues. HANPs also decreased Cd mobility in soil, retaining it in fractions less available for plant uptake. Germination rates differed between pot experiments and phytotoxicity assays, although the first demonstrated greater Cd immobilization in HANP-treated soils, resulting in reduced Cd translocation to quinoa shoots. These findings highlight the potential of HANPs as an effective tool for remediating Cd-contaminated soils, thereby improving soil pollution, crop safety, and quality for human consumption.